PERAN GURU AKIDAH AKHLAK DALAM MEMBENTUK KARAKTER PESERTA DIDIK KELAS XI MAS AL – MAHDI SERANG BANTEN - Sunardi (UNISAN JURNAL, 2024)
This exploration means to investigate data about the job of moral aqidah educators in molding the personality of class XI MAS Al-Mahdi Serang Banten understudies. The strategy utilized is a contextual investigation with information assortment procedures through meetings and perception. The examination results show that in view of the outcomes and conversation of exploration in regards to the job of moral conviction educators in forming understudy character in the homeroom, moral conviction instructors should can give a decent comprehension of religion and ethics, utilizing proper learning. procedures, and including guardians in forming the personality of understudies. Intriguing and intuitive learning methodologies can assist understudies with figuring out strict and moral ideas. Including guardians can further develop correspondence among instructors and guardians, so it can assist with forming understudy character